2020
DOI: 10.1111/idh.12479
|View full text |Cite
|
Sign up to set email alerts
|

Are diabetes and dental care providers in the Republic of Mauritius advising patients about the importance of oral health in diabetes management?

Abstract: Diabetes and dental care providers may greatly contribute in the early detection of oral diseases and diabetes, respectively, and in the prevention of complications of diabetes. However, there is limited collaboration and referrals between these two groups of health professionals. Objective To investigate whether diabetic providers are addressing the importance of oral care in the management of diabetes and whether dental care providers are advising their patients with diabetes about the importance of glycaemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Multiple studies have shown that patients with diabetes are more likely to receive education about the relationship between oral health and diabetes from their dental providers than from their medical provider. 32 All health professionals working in the hospital inpatient setting reported online referral pathways would increase the likelihood of referring a patient to the dentist. This reflects the established digital interdepartmental referral pathway used by hospital staff.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Multiple studies have shown that patients with diabetes are more likely to receive education about the relationship between oral health and diabetes from their dental providers than from their medical provider. 32 All health professionals working in the hospital inpatient setting reported online referral pathways would increase the likelihood of referring a patient to the dentist. This reflects the established digital interdepartmental referral pathway used by hospital staff.…”
Section: Discussionmentioning
confidence: 99%
“…Referral of patients with diabetes to a dental clinic gives rise to treatment and clinical intervention opportunities, and for the dental team to educate the patient in preventative practices. Multiple studies have shown that patients with diabetes are more likely to receive education about the relationship between oral health and diabetes from their dental providers than from their medical provider 32 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They also supported their health and medical counterparts to refer patients for dental check-up and treatment for the prevention of oral diseases. In addition, the patients must be informed through consistent messages by all members of the healthcare professional team regarding the equally crucial role of disease management for both diseases [ 22 56 ] as they could affect one another as a result of the up-regulated inflammation from each disease.…”
Section: Discussionmentioning
confidence: 99%
“…of the healthcare professional team regarding the equally crucial role of disease management for both diseases [22,56] as they could affect one another as a result of the upregulated inflammation from each disease. The emergence of non-evidence-based remedies and uncertified products easily available in the market has posed a challenge for the delivery of conventional treatment prescribed by healthcare professionals [50,57].…”
Section: Prioritising Time For Counselling Sessionsmentioning
confidence: 99%